Analisis Kelayakan Sistem Tumpangsari Jagung (Zea mays L.) dan Kacang Tanah (Arachis hypogea L.) di Kecamatan Lawa Kabupaten Muna Barat - Arisman, Arisman; Saediman, Saediman; Abdullah, Weka Gusmiarty (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
Feasibility of the Intercropping Systems of Maize (Zea mays L.) and Peanuts (Arachis hypogea L.) in Wamelai Village, Lawa Subdistrict, West Muna District" Under the supervision of H. Saediman as Lead Advisor and Weka Gusmiarty Abdullah, as Co-Advisor. The purpose of this study was to assess the returns and to ascertain the feasibility, of intercropping systems of maize and peanut in Wamelai Village, Lawa Sub-District, West Muna District. The data used in this study include primary data and secondary data. Data were collected through observation, interviews, recording, and documentation. Variables being investigated consisted of farmers’ characteristics (age, level of education and household size), size of landholding (ha), production costs, revenue, net returns, and feasibility of the intercropping systems. Data were analyzed using cost and returns analysis and R/C ratio. The research results showed that the intercropping systems of maize (Zea mays L.) and peanut (Arachis hypogea L.) in Wamelai village, Lawa sub-district, west Muna district was profitable with the net returns of Rp4,084,887 per cropping season. The intercropping of maize and peanut in the study village was feasible based on the R/C ratio of 4.84. Keywords; farming, feasibility, intercropping, maize, peanuts.